Design and evaluation of rhubarb total free anthraquinones oral colon-specific drug delivery granules to improve the purgative effect - Hongwei Wei; Jinhua Chang; Pei Liu; Zhongsi Li; Guangxin Miao; Xigang Liu; Cuizhe Liu; Xiangrong Zhang
Rhubarb is commonly used as a cathartic in Asian countries. However, researchers have devotedextensive concerns to the quality control and safety of rhubarb and traditional Chinese preparations composed of rhubarb due to the instable purgative effect and potential nephrotoxicity of anthraquinones. In this study, we aimed to prepare rhubarb total free anthraquinones (RTFA) oral colon-specific drug delivery granules (RTFA-OCDD-GN) to delivery anthraquinones to colon to produce purgative effect. RTFA-OCDD-GN were prepared using chitosan and Eudragit S100 through a double-layer coating process and the formulation was optimized. Continuous release studies were performed in a simulated gastric fluid (pH 1.2), followed by a small-intestinal fluid (pH 6.8) and a colonic fluid (pH 7.4, containing rat cecal contents). The purgative effect test was performed in rats. The dissolution profile of RTFA-OCDD-GN showed that the accumulative dissolution rate of RTFA was about 83.0% in the simulated colonic fluid containing rat cecal contents and only about 9.0% in the simulated gastrointestinal fluids. And the RTFA-OCDD-GN could produce the comparative purgative activity as rhubarb, suggesting it could deliver the free AQs to the colon. The RTFA-OCDD-GN was a useful media to enhance the purgative activity of free anthraquinones after administered orally.